Deradikalisasi Sebagai Bentuk Pencegahan Tindak Pidana Terorisme di Indonesia (Studi Kasus Putusan Mahkamah Agung Nomor 4345 K/Pid.Sus/2022) - Sokhibul Amin; Feny Windiyastuti (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
One of the cases of criminal acts of terrorism that reflects efforts to deradicalize the accused or convict is the Supreme Court Decision Number 4345 K/Pid.Sus.2022. The purpose of this research is to see how the deradicalization program is carried out as a form of preventing criminal acts of terrorism in Indonesia. This research is included in normative legal research using descriptive qualitative research methods. The approach used is the approach of statutory regulations. The results of the study concluded that the deradicalization program was carried out through 4 (four) stages, namely Identification and Assessment, Rehabilitation, Re-eduction, and Social Reintegration aimed at parties in conflict with the law, such as suspects, accused, convicts, convicts, ex-convicts, and people or groups who exposed to radical terrorism. The Supreme Court Decision Number 4345 K/Pid.Sus.2022 implicitly conveys a message that the Supreme Court supports the deradicalization program because it does not comply with the demands of the Public Prosecutor who wants life imprisonment for the defendant. This is in line with the deradicalization program for terrorism convicts which is being optimized by the Government. This is because life imprisonment closes the final stage of the deradicalization program. As for some of the obstacles or obstacles in the implementation of the deradicalization program in general, that is due to two factors, namely internal factors and external factors. Internal factors such as lack of human resources, lack of synergy between agencies/ministry related to counter-terrorism. While external factors include Indonesia's vast and difficult to reach geographical location, several terrorist groups do not want to cooperate in eradicating their networks, as well as policy misalignment between institutions related to terrorism prevention